Imipramine Treatment Alters Sphingomyelin, Cholesterol, and Glycerophospholipid Metabolism in Isolated Macrophage Lysosomes - Jacob M. Albright; Matthew J. Sydor; Jonathan Shannahan; Christina R. Ferreira; Andrij Holian (Biomolecules, 2023)
Lysosomes are degradative organelles that facilitate the removal and recycling of potentially cytotoxic materials and mediate a variety of other cellular processes, such as nutrient sensing, intracellular signaling, and lipid metabolism. Due to these central roles, lysosome dysfunction can lead to deleterious outcomes, including the accumulation of cytotoxic material, inflammation, and cell death. We previously reported that cationic amphiphilic drugs, such as imipramine, alter pH and lipid metabolism within macrophage lysosomes. Therefore, the ability for imipramine to induce changes to the lipid content of isolated macrophage lysosomes was investigated, focusing on sphingomyelin, cholesterol, and glycerophospholipid metabolism as these lipid classes have important roles in inflammation and disease. The lysosomes were isolated from control and imipramine-treated macrophages using density gradient ultracentrifugation, and mass spectrometry was used to measure the changes in their lipid composition. An unsupervised hierarchical cluster analysis revealed a clear differentiation between the imipramine-treated and control lysosomes. There was a significant overall increase in the abundance of specific lipids mostly composed of cholesterol esters, sphingomyelins, and phosphatidylcholines, while lysophosphatidylcholines and ceramides were overall decreased. These results support the conclusion that imipramine’s ability to change the lysosomal pH inhibits multiple pH-sensitive enzymes in macrophage lysosomes.